Application of the wavelet transform in problems of searching for a damaged connection with a single-phase earth fault according to SV-stream data - A. O. Paramzin; S. Yu. Dolinger (Вестник Северо-Кавказского федерального университета, 2024)
Introduction. Research relevance is conditioned by the necessity to increase selectivity of protection and signaling devices for single-phase ground faults in 6-10 kV networks. Single-phase ground faults are one of the prevailing causes of equipment failures in the oil and gas production sector of Russia, which is the backbone of the economy.Goal. The article aims is veriﬁcation of the possibility of using the Sample Value data of IEC 61850 in the tasks of ﬁnding a faulty feeder with single-phase earth fault by means of wavelet transform.Materials and methods. Wavelet transform with decomposition to the 6th level of zero-sequence current 3i0. Interpolation of SV-ﬂow data. Determination of eﬀective values of higher harmonic currents by wavelet coeﬃcients.Results and discussion. The magnitude of the relative deviation of the calculated eﬀective values of the higher harmonic currents between the data of the current sensor with a sampling frequency of 12,800 Hz and the interpolated values of the SV ﬂow with an increased frequency from 4,000 to 12,800 Hz was 1.18 % with damage to the connection feeding the nonlinear load and 2.86 % in the experiment with a sinusoidal load.Conclusion. Experimental results show that the highest value of the sum of the higher harmonic currents corresponds to the feeder with the presence of a single-phase ground fault. The limited number of samples per period poses the challenge of interpolating the Sampled Value data up to a frequency of 12 800 Hz.